Adverse childhood experiences and intimate partner violence during pregnancy and their association to postpartum depression - Mahenge, Bathsheba; Stöckl, Heidi; Mizinduko, Mucho; Mazalale, Jacob; Jahn, Albrecht (Journal of affective disorders, 2018)
Background - Adverse childhood experiences (ACEs) and intimate partner violence (IPV) are recognized global health problems. Both ACEs and IPV have been linked to adverse physical and mental health problems for both mothers and infants. The aim of this study was to determine the prevalence of physical and/or sexual ACEs and IPV and their association to symptoms of postpartum depression among postpartum women in sub-Saharan Africa. - Methods - A cross-sectional survey was conducted in three health centers in the three districts of Dar es Salaam, comprising Ilala, Kinondoni and Temeke. A total of 500 women were interviewed by two trained midwife nurses during their routine postnatal care. The women were asked about their experiences of adverse childhood experiences, intimate partner violence and symptoms of postpartum depression. - Results - Of the 500 women who were interviewed, 39.4% (n = 197) reported to have experienced physical and/or sexual ACE and 18.8% (n = 94) experienced physical and/or sexual IPV during their index pregnancy. Physical ACE (AOR 2.6, 95% CI: 1.50-4.57), sexual ACE (AOR 2.7, 95% CI: 1.35-5.41), physical IPV (AOR 5.8, 95% CI: 2.98-11.43) and Sexual IPV (AOR 5.5, 95%CI: 2.51, 12.09) were significantly associated with symptoms of postpartum depression. - Conclusion - Four out of ten women reported to have experienced ACEs and two out of ten women reported IPV in the index pregnancy which was significantly associated with symptoms of postpartum depression. These results are alarming and call upon the attention of health workers and the community at large in prevention, screening and early intervention of ACEs, IPV and symptoms of postpartum depression.